3 - Performative Injunctions in the Higher Education Body: The Discursive Career of Research Capacity Development in a South African University Faculty of Education: par Aslam Fataar - Fataar, Aslam (Journal of Higher Education in Africa, 2022)
This article discusses Research Capacity Development (RCD), in a Faculty of Education at a South African university. It employs the notions of performativity and performance to argue that specific local sites at universities have complex stories to tell about their responsiveness to research output imperatives. The article emphasizes that there is a formative relationship between the specific RCD discursive text of this Faculty and the performance- based activities of its management and academics. The career of RCD in the Faculty is established in the light of specific activities against the background of a small Faculty environment. The article specifically considers the basis for its relative success in the area of doctoral completion by its academic staff and its diminishing article writing output. It draws the conclusion that efforts to secure a vigorous RCD platform depend on the ability to establish a nurturing institutional environment in which a scholarly culture can be encouraged and protected.